2006
DOI: 10.1002/ijc.21843
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 5‐fluorouracil chemosensitivity of liver metastases from colorectal cancer using primary tumor specimens: Three‐gene expression model predicts clinical response

Abstract: We identified genes related to 5-fluorouracil (5-FU) sensitivity in colorectal cancer and utilized these genes for predicting the 5-FU sensitivity of liver metastases. Eighty-one candidate genes involved in 5-FU resistance in gastric and colon cancer cell lines were previously identified using a cDNA microarray. In this study, the mRNA expression levels of these 81 selected genes and the genes of 5-FUrelated enzymes, including thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD) and orotate phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Previous clinical studies also revealed the positive expression and activity of OPRT to be associated with the responsiveness to 5-FU in a variety of human cancers, including colorectal cancers (Isshi et al, 2002;Fujii et al, 2003;Ichikawa et al, 2003a;Matsuyama et al, 2006) and bladder carcinomas (Mizutani et al, 2004). However, these studies were performed using relatively small number of patients, and then were evaluated by biochemical assays for OPRT enzyme activity or reverse transcriptional PCR (RT -PCR) assays for OPRT gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies also revealed the positive expression and activity of OPRT to be associated with the responsiveness to 5-FU in a variety of human cancers, including colorectal cancers (Isshi et al, 2002;Fujii et al, 2003;Ichikawa et al, 2003a;Matsuyama et al, 2006) and bladder carcinomas (Mizutani et al, 2004). However, these studies were performed using relatively small number of patients, and then were evaluated by biochemical assays for OPRT enzyme activity or reverse transcriptional PCR (RT -PCR) assays for OPRT gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…5-fluorouracil (5-FU), or a related fluoropyrimidine, has been used as a component of the therapeutic regimen for colon cancer patients for four decades. [3][4][5] However, despite a combination of 5-FU with other chemotherapeutic agents, the clinical response rate for patients with liver metastases remains 20-39%, 6 indicating a need for a more effective regimen. The Par-4 protein was first identified in prostate cancer cells that were induced to undergo apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…1,[8][9][10][19][20][21][22] Recently, additional enzymes important in 5-FU effects have been identified, including mRNA expression of TNFRSF1B, SLC35F5, and orotate phosphoribosyltransferase. [23][24][25] At the DNA level, a tandem repeat of 28 bp is present in the 5 0 -untranslated region of the TS gene and is linked to its expression and enzymatic activity in tumors. An increase in mRNA and protein has been reported in patients with three repeats (3R) as compared with two repeats (2R).…”
Section: Markers For Fluoropyrimidinesmentioning
confidence: 99%